CSF Pressure Change in Relation to Opening Pressure and CSF Volume Removed - Griffith, B.; Capobres, T.; Patel, S.C.; Marin, H.; Katramados, A.; Poisson, L.M. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Idiopathic intracranial hypertension is a complex neurologic disorder resulting from increased intracranial pressure. Our aim was to determine whether a correlation exists between the CSF pressure-volume relationship, specifically the craniospinal elastance and pressure-volume index, in patients with idiopathic intracranial hypertension and whether opening pressure affects this relationship.MATERIALS AND METHODS: Lumbar punctures performed for suspected idiopathic intracranial hypertension from 2006 to 2017 were identified. Opening and closing pressures, CSF volume removed, and clinical diagnosis of idiopathic intracranial hypertension were obtained from the medical records. The craniospinal elastance (pressure change per milliliter of CSF removed) and pressure-volume index were calculated, and the Pearson correlation coefficients between both the craniospinal elastance and pressure-volume index and opening pressure were determined. Linear regression models of craniospinal elastance and the pressure-volume index and interaction terms with opening pressure were assessed for covariate influence on this association.RESULTS: One hundred sixteen patients were included in the final analysis. The mean craniospinal elastance according to opening pressure group was 0.52 ± 0.18 for <20 cm H2O, 0.57 ± 0.20 for 20–29 cm H2O, 0.91 ± 0.28 for 30–39 cm H2O, and 1.20 ± 0.25 for ≥40 cm H2O. There was a positive linear association between opening pressure and craniospinal elastance with a 0.28 cm H2O/mL increase in craniospinal elastance (standard error = 0.03, P < .001) for every 10 cm H2O increase in opening pressure. Of the covariables analyzed, only age older than 50 years and total volume of CSF removed affected this association.CONCLUSIONS: As opening pressure increases, the craniospinal elastance increases in a linear fashion while the pressure-volume index decreases. Further studies are needed to determine whether these changes relate to the underlying pathophysiology of idiopathic intracranial hypertension or simply represent established CSF volume pressure dynamics.BMIbody mass indexΔP/ΔVpressure change per milliliter of CSF removedEcscraniospinal elastanceICPintracranial pressureIIHidiopathic intracranial hypertensionLPlumbar punctureOPopening pressurePVIpressure-volume index